(3QSGdI aj GdcdGe Ydi Ci GdeTOOIs - (3YKeGf Hf CMeO Hf SYjO Hf YKeGf Hf bGFO GdfLOj,J (B1097 (3g` s ((3GdcJHNGfI GdNOjhjI (B_ (3eUQ s)
(3ChdgG (B:s
(3GdMeO ddg QGaY GdeTcdGJ Yf Chdi GdCdHGH hHYO ajbhd YKeGf Hf CMeO GdfLOi GdMfHdi gPg ahGFO JJYdb HCi GdeTOOI GdjGA ef cdeGJ GdYQHjI JhVM eG ajgG ef CbSGe hCMcGe MJi JUjQ NajGJgG LdjI s
(3BNQgG (B:s
(3aEfgG dGJYQH Hd JHfi heG Shi gPg GdUhQI JYQH Ci ajgG aUhQI GdHfGA Od YdjgG eaghe GdcdGe hUhQ GdEYQGH Od YdjgG efWhbg LYdfG Gddg HJbHdg hEjGce ef GdfGWbjf HGdNjQ GdUGeJjf Yf GdZjQ hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B202 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B249s
Keywords: (3GdfMhs